Ophthalmic Manifestations in Children and Young Adults with Down Syndrome and Congenital Heart Defects. (17th March 2015) - Ljubic, Antonela; Trajkovski, Vladimir; Tesic, Milorad; Tojtovska, Biljana; Stankovic, Branislav
ABSTRACT: Purpose : To investigate whether different types of ocular manifestations are associated with congenital heart disease (CHD) in a large Caucasian population of children and young adults with Down syndrome (DS). Methods : Population-based, case-control study which included 185 subjects with DS (mean age 13.2 ± 7.9 years), who reported presence or absence of CHD; DS with CHD group (51 subjects, mean age 10.6 ± 5.6 years) and DS without CHD (134 subjects, mean age 14.2 ± 8.4 years). Results : In our sample with DS and CHD, strabismus was found in 15 subjects (29.4%), nystagmus in 1 (2.0%), epiblepharon in 21 (41.2%) and Brushfield spots in 15 (31.3%). In the DS without CHD group, strabismus was found in 38 participants (28.4%), nystagmus in 13 (9.7%), epiblepharon in 31 (23.5%) and Brushfield spots in 21 (16.0%). Only the variables epiblepharon and presence of Brushfield spots differed significantly between the two groups ( p  = 0.02 and p  = 0.03, respectively). Hyperopia was present in 26 participants (53.1%) in the DS with CHD group, and in 65 (57.0%) in the DS without CHD group. Oblique astigmatism was present in 25 (52.1%) in the DS with CHD group and in 61 (53.5%) in the DS without CHD group. Conclusions : Frequencies of DS participants presenting with strabismus, nystagmus, hyperopia and oblique astigmatism were not statistically different between those with CHD and those without CHD in this sample. Further studies are needed to confirm if there are associations between the presence of Brushfield spots or epiblepharon and CHD in patients with DS.